Observation of CuPt-type ordered structure in CdZnTe during organometallic vapor phase epitaxial growth - Kwon, MS; Lee, JY; Suh, SH (The Japan Society of Applied Physics, 1998)
A CuPt-type ordered structure in CdZnTe has been observed in HgCdTe/CdxZn1-xTe/GaAs grown by interdiffused multilayer processing. Selected area electron diffraction and cross-sectional, high-resolution transmission electron microscopy have been employed to identify the ordered structure in CdZnTe. Selected area electron diffraction patterns showed two sets of (1/2 1/2 1/2) extra spots with symmetrical intensity through [110] projection, but no extra spots through [(1) over bar 10] projection. In the [110] projection, high-resolution images of ordered CdZnTe showed the doubling periodicity along [(1) over bar 11] or [1(1) over bar1$] through [110] projection. It was determined that the two variants of CuPt-type ordered-CdZnTe were formed on (1) over bar 11) or (1(1) over bar1$ through [110] projection. The two variants were observed with almost equal probability and had similar domain structures.